The power of prophecy; Prince Dipanagara and the end of an old order in Java, 1785-1855 - Carey, Peter (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2008)
National hero, Javanese mystic, pious Muslim and leader of the 'holy war' against the Dutch between 1825 and 1830, the Yogyakarta prince, Dipanagara (1785-1855, otherwise known as Diponegoro), is pre-eminent in the pantheon of modern Indonesian historical figures. Yet despite instant name recognition in Indonesia, there has never been a full biography of the prince's life and times based on Dutch and Javanese sources. 'The power of prophecy' is a major study which sets Dipanagara's life history against the context of the turbulent events of the late eighteenth and early nineteenth century when the full force of European imperialism hit Indonesia like an Asian tsunami destroying forever Java's 'old order' and propelling the twin forces of Islam and Javanese national identity into a fatal confrontation with the Dutch. This confrontation known as the Java War, in which Dipanagara was defeated and exiled, marked the beginning of the modern colonial period in Indonesia which lasted until the Japanese occupation of 1942-1945. The book presents a detailed analysis of Dipanagara's pre-war visions and aspirations as a Javanese Ratu Adil ('Just King') based on extensive reading of his autobiography, the Babad Dipanagara as well as a number of other Javanese sources. Dutch and British records, in particularly the Residency Archives of Yogyakarta and Surakarta currently kept in the Indonesian National Archives, provide the backbone of this scholarly work. The book will be read with profit by all those interested in the rise of Western colonial rule in Indonesia, the fate of indigenous cultures in an age of imperialism and the role of Javanese Islam in modern Indonesian history. Peter Carey, Laithwaite tutor in History at Trinity College, Oxford, has made a lifetime study of Dipanagara and the history of early nineteenth century Java. His many works include the two-volume Archive of Yogyakarta (1980, 2000), The British in Java, 1811-1816; A Javanese account (1992) and Babad Dipanagara; An account of the outbreak of the Java War (1825-1830) (1981). He is one of Britain's foremost historians of Southeast Asia and has also published on Cambodia, Burma and East Timor.